2018
DOI: 10.3390/w10091114
|View full text |Cite
|
Sign up to set email alerts
|

Operational Evaluation of a Small Hydropower Plant in the Context of Sustainable Development

Abstract: Proper design of hydrotechnical structures should meet the basic principles of sustainable development, i.e., the investment should be designed and made in technical terms, in accordance with the applicable standards and regulations, provide certain economic benefits and guarantee the absence of environmental hazards. The article examines the work of a Small Hydropower Plant (SHP) in Jaracz in technical and hydraulic terms. It also provides the analysis of the effect of changes in parameters such as water head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
0
14
0
2
Order By: Relevance
“…5% of the cross-section. With regard to corresponding coverage of the cross section by plant debris [34], it was observable that the water level decreased by 0.05 m. Szabo-Meszaros et al [49] indicated that hydraulic losses on clean trash racks can reach 0.05 m depending on the trash racks designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5% of the cross-section. With regard to corresponding coverage of the cross section by plant debris [34], it was observable that the water level decreased by 0.05 m. Szabo-Meszaros et al [49] indicated that hydraulic losses on clean trash racks can reach 0.05 m depending on the trash racks designs.…”
Section: Resultsmentioning
confidence: 99%
“…The input of small hydropower plants (SHP) can be adversely affected by numerous factors obstructing their operation [33,34], i.e., flooding, inundation, hurricanes, heavy rain and snow load.…”
Section: Introductionmentioning
confidence: 99%
“…For different water levels, debris parameters change. At low and medium flows, mainly leaves, twigs, fragments of macroliths, i.e., fine organic materials, are transported [51]. When a surge occurs, blades of dry grasses, tree trunks located on slopes, and branches are transported.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, physical reliability of the power plant will be compromised. The efficiency and cost to hire manpower can also influence the reliability of the power plant . Skilled manpower will attract more expenditure compared to that of unskilled manpower, but the system efficiency will increase due to the involvement of the expertise of the skilled employee in the system.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency and cost to hire manpower can also influence the reliability of the power plant. 7 Skilled manpower will attract more expenditure compared to that of unskilled manpower, but the system efficiency will increase due to the involvement of the expertise of the skilled employee in the system. The rate of selling electricity and cost incurred for power production are the other two drivers of reliability in the power plant.…”
Section: Introductionmentioning
confidence: 99%